2011
DOI: 10.1038/nn.2986
|View full text |Cite|
|
Sign up to set email alerts
|

A catalytically silent FAAH-1 variant drives anandamide transport in neurons

Abstract: The endocannabinoid anandamide is removed from the synaptic space by a selective transport system, expressed in neurons and astrocytes, which remains molecularly uncharacterized. Here we describe a partly cytosolic variant of the intracellular anandamide-degrading enzyme, fatty acid amide hydrolase-1 (FAAH-1), termed FAAH-like anandamide transporter (FLAT), which lacks amidase activity but binds anandamide with low micromolar affinity and facilitates its translocation into cells. Known anandamide transport inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
144
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(146 citation statements)
references
References 48 publications
0
144
1
Order By: Relevance
“…Although this model supports the existence of a plasma membrane-localized AEAbinding protein, it cannot explain why uptake inhibitors also affect AEA efflux. Right after the identification of several cytosolic AEA "chaperone" proteins, such as FABP5, FABP7, Hsp70, albumin, and the more controversial FLAT (274,415,637,773), a revised version of the simple diffusion model was proposed. According to this model, the passive diffusion process of AEA across the membrane is followed by intracellulaer carrier-mediated transport to effector proteins, catabolic enzymes, and sequestration sites (268,270).…”
Section: Endocannabinoid Biosynthesis and Degradationmentioning
confidence: 99%
“…Although this model supports the existence of a plasma membrane-localized AEAbinding protein, it cannot explain why uptake inhibitors also affect AEA efflux. Right after the identification of several cytosolic AEA "chaperone" proteins, such as FABP5, FABP7, Hsp70, albumin, and the more controversial FLAT (274,415,637,773), a revised version of the simple diffusion model was proposed. According to this model, the passive diffusion process of AEA across the membrane is followed by intracellulaer carrier-mediated transport to effector proteins, catabolic enzymes, and sequestration sites (268,270).…”
Section: Endocannabinoid Biosynthesis and Degradationmentioning
confidence: 99%
“…(4) FLAT was reported as a critical molecular component of anandamide transport in neural cells [44]. The study showed that FLAT is a catalytically silent splice variant of FAAH, is expressed robustly throughout the brain, and facilitates the translocation of anandamide into cells.…”
Section: Other Possible Mechanismsmentioning
confidence: 99%
“…Moving to the inhibition of endocannabinoid cellular uptake, there are some potential therapeutic effects observed with the use of membrane transporter inhibitors in animal models (30,38,40). This approach has once again gained attention after the recent discovery of FAAH-like anandamide transporter (49), but clinical research remains to be determined.…”
Section: Modulation Of the Endocannabinoid Systemmentioning
confidence: 99%